Pengaruh Strategi Pemasaran Produk Kopi Irish Terhadap Keputusan Pembelian di Kopi Kadeudeuh Kabupaten Sumedang - Nuslih Jamiat; Zeniva Reimelda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Kopi Kadeudeuh is a coffee shop built in the middle of downtown Sumedang. But now there are many other coffee shops that have sprung up in Sumedang and other cities in Indonesia. Marketing is not just marketing products, but also requires the right strategy. Because marketing strategy is the key to the success of a company in increasing the number of customers. The purpose of this study is to determine the influence of marketing strategies applied by Kopi Kadeudeuh. This study used quantitative descriptive research method by collecting information through interviews and surveys (questionnaires) to 100 respondents visiting Kopi Kadeudeuh. The results of this study show that marketing strategies are very influential on purchasing decisions in a business, especially coffee shops. The results of this study show that Kopi Kadeudeuh has implemented effective marketing strategies in aspects of product, price, place, promotion, people, process, and physical evidence. High quality Irish Coffee products, affordable and competitive prices, strategic location, attractive promotions, friendly and fast service, easy ordering process, and comfortable place design are factors that influence consumer purchasing decisions. However, the promotional aspect still needs to be improved, especially in the use of social media and more attractive discount programs.